Emerging drugs for the prevention of migraine. (3rd July 2021) - Ogunlaja, Oyindamola; Karsan, Nazia; Goadsby, Peter
ABSTRACT: Introduction: Migraine is a common and disabling neurological disorder. A greater understanding of the pathophysiological mechanisms underlying migraine has led to the availability of specific new drugs targeting calcitonin gene-related peptide (CGRP). The success of the CGRP inhibitors validates research efforts into migraine-specific therapies. Areas covered: There are additional promising therapeutic targets that will be covered in this paper, focusing on the pain phase. They include pituitary adenylate cyclase-activating polypeptide (PACAP), the orexinergic system, the nitric oxide signaling pathway specifically neuronal nitric oxide synthase inhibitors (nNOSi), and metabotropic glutamate receptor 5 (mGluR5). Expert opinion: Based on currently available research; the targets discussed in this paper are all on equal footing with each other in terms of their potential as effective novel migraine therapies. There is a need for more clinical trials to pinpoint which of these potential drug targets will be effective for migraine preventio.